2002
DOI: 10.1590/s0102-311x2002000100011
|View full text |Cite
|
Sign up to set email alerts
|

A reprodução social da hanseníase: um estudo do perfil de doentes com hanseníase no Município de São Paulo

Abstract: This study discusses the relationship between work and living conditions among leprosy patients enrolled in the São Paulo municipal public health system in 1996. Social patterns were studied based on the theory of social determination of the health-disease process. The main purpose of the study was to emphasize evidence of the disease determination network, seeking new knowledge to improve public policies on leprosy. Data were gathered from a sample of leprosy patients registered in the city's public health sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
(5 reference statements)
1
6
1
17
Order By: Relevance
“…The study of social reproduction of leprosy in the city of São Paulo identified that most affected people were in intermediate and inferior bracket, working in informal, underpaid and unskilled jobs, corroborating the data observed here (5) .…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The study of social reproduction of leprosy in the city of São Paulo identified that most affected people were in intermediate and inferior bracket, working in informal, underpaid and unskilled jobs, corroborating the data observed here (5) .…”
supporting
confidence: 88%
“…of those surveyed had family income higher than 1.8 minimum salary, a percentage that was higher than that observed here, once 32% of patients presented this family income (5) .…”
contrasting
confidence: 73%
See 2 more Smart Citations
“…A hanseníase é fortemente relacionada às condições socioeconômicas 23 , ao crescimento acelerado da população dessas áreas, ao deslocamento de contingente populacional de áreas rurais para as cidades, que pode não ter sido acompanhado de melhoria da estrutura urbana com conseqüente declínio nas condições de vida dessas populações.…”
Section: Discussão E Conclusãounclassified